2000
DOI: 10.1111/j.1349-7006.2000.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction of TZT‐1027, a Potent Antitumor Agent, with Tubulin

Abstract: TZT‐1027, a derivative of dolastatin 10 isolated from the Indian Ocean sea hare Dolabella auricularia in 1987 by Pettit et al. , is a potent antimicrotubule agent. We have compared the activity of TZT‐1027 with that of dolastatin 10 as well as the vinca alkaloids vinblastine (VLB), vincristine (VCR) and vindesine (VDS). TZT‐1027 and dolastatin 10 inhibited microtubule polymerization concentration‐dependently at 1–100 μ M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…One of the more interesting, which we also prepared in a radiolabeled form, is auristatin-PE (24) (Fig. 1), also prepared independently as TZT-1027 (25). We began to study the potential of direct photoaffinity labeling with the [ 3 H]dolastatin 10 1 and the [ 3 H]auristatin-PE to provide information about the binding site for these peptides on tubulin.…”
mentioning
confidence: 99%
“…One of the more interesting, which we also prepared in a radiolabeled form, is auristatin-PE (24) (Fig. 1), also prepared independently as TZT-1027 (25). We began to study the potential of direct photoaffinity labeling with the [ 3 H]dolastatin 10 1 and the [ 3 H]auristatin-PE to provide information about the binding site for these peptides on tubulin.…”
mentioning
confidence: 99%
“…TZT-1027 is a novel antitumour agent that inhibits microtubule polymerisation and exhibits potent antitumour activity in preclinical models (Miyazaki et al, 1995;Kobayashi et al, 1997;Natsume et al, 2000Natsume et al, , 2003Natsume et al, , 2006Otani et al, 2000;Watanabe et al, 2000Watanabe et al, , 2006a. We investigated the effect of TZT-1027 on cell cycle progression with the use of tsFT210 cells, which can be synchronised in G 2 phase by incubation at 39.41C and consequent inactivation of Cdc2 (Osada et al, 1997;Tamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…TZT-1027 inhibits microtubule assembly by binding to tubulin (Kobayashi et al, 1997;Natsume et al, 2000). In vitro, it inhibits the growth of various human cancer cells at low concentrations .…”
mentioning
confidence: 99%
“…25 They share the same binding site and have similar affinities, 14,28 whereas additional binding sites have either high affinities (Kd: 1-2 mmol) or low affinities (Kd: 0.25-3 mmol). 24 Previous studies have also reported that dolastatins can also bind at different sites from those used by Vinca alkaloids 14,29 These additional binding sites might be responsible for the differences in genomic response induced by the dolastatins and Vinca alkaloids.…”
Section: Characterization Of Tzt-1027 In Reference Profilingmentioning
confidence: 98%
“…TZT-1027 is a mitotic spindle poison that interacts with tubulin at the Vinca alkaloids binding site, 14 but the spectra of antitumor activity of TZT-1027 and the Vinca alkaloids are different in vivo. 7,10,15 TZT-1027 also showed potent antitumor activity against a vincristine-resistant cell line.…”
Section: Introductionmentioning
confidence: 99%